Electrical treeing in XLPE cable insulation at cryogenic temperature under harmonic AC voltages. (October 2015) - Mittal, Lakshya; Sarathi, R.; Sethupathi, K.
Highlights: Fibrillar type electrical trees formed under harmonic AC voltages. The voltage profile have high influence on electrical tree formation. Tree inception and propagation radiates UHF signal. Rate of rise of voltage and peak factor have high influence on tree growth. Abstract: The shape of electrical trees formed in XLPE cable insulation at low temperature under AC and harmonic voltages are fibrillar type. Life of cable insulation failure due to electrical treeing was analysed through Weibull distribution studies. It is observed that the voltage wave shape and peak factor exhibit high influence on the life of cable insulation due to electrical treeing. Harmonics with higher THD's and the failure rate of cable insulation due to treeing are the same. The presence of 4th and 5th harmonics in supply voltage could cause early failure of cable insulation. Ultra High Frequency (UHF) signal radiated during tree growth process, under harmonic voltages lies in the range 0.5–1.5 GHz. Phase Resolved Partial Discharge (PRPD) analysis using spectrum analyser has revealed that under 50 Hz, discharges occur near zero crossing and in the presence of harmonics, it occurs when the rate of voltage rise is high. The discharge occurs at its peak under low frequency AC voltage of 1 Hz.